AcEXPA1, an α-expansin gene, participates in the aluminum tolerance of carpetgrass (Axonopus compressus) through root growth regulation - Li, Jifu; Liu, Liting; Wang, Linjie; Idupulapati, Rao; Wang, Zhiyong; Chen, Zhijian (Springer, 2024)
Aluminum (Al) toxicity is a major mineral toxicity that limits plant productivity in acidic soils by inhibiting root growth. Carpetgrass (Axonopus compressus), a dominant warm-season turfgrass widely grown in acidic tropical soils, exhibits superior adaptability to Al toxicity. However, the mechanisms underlying its Al tolerance are largely unclear, and knowledge of the functional genes involved in Al detoxification in this turfgrass is limited. In this study, phenotypic variation in Al tolerance, as indicated by relative root elongation, was observed among seventeen carpetgrass genotypes. Al-responsive genes related to cell wall modification were identified in the roots of the Al-tolerant genotype ‘A58’ via transcriptome analysis. Among them, a gene encoding α-expansin was cloned and designated AcEXPA1 for functional characterization. Observed Al dose effects and temporal responses revealed that Al induced AcEXPA1 expression in carpetgrass roots. Subsequently, an efficient and convenient Agrobacterium rhizogenes-mediated transformation method was established to generate composite carpetgrass plants with transgenic hairy roots for investigating AcEXPA1 involvement in carpetgrass root growth under Al toxicity. AcEXPA1 was successfully overexpressed in the transgenic hairy roots, and AcEXPA1 overexpression enhanced Al tolerance in composite carpetgrass plants through a decrease in Al-induced root growth inhibition. Taken together, these findings suggest that AcEXPA1 contributes to Al tolerance in carpetgrass via root growth regulation.